2007
DOI: 10.1111/j.1365-2362.2007.01849.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of oxidative stress and PON1 with LDL and HDL particle size in middle‐aged subjects

Abstract: Even in the absence of symptoms of atherosclerosis, sdLDL particles are associated with increased oxidative stress, which may stimulate a compensatory rise in PON1 DZOase activity. Elevated oxidative stress may significantly affect HDL subclass distribution, resulting in the accumulation of smaller, denser HDL particles with diminished antioxidative capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 53 publications
(67 reference statements)
4
30
0
1
Order By: Relevance
“…Consistent with our findings, NLA was also increased in patients with coronary artery disease (CAD) (24). Recent studies have shown that HDLs from CAD patients enriched in PON1 (53) and proatherogenic small and density LDLs tend to be associated with increased PON1 activity (54). Based on these findings, we speculate that PCOS-related changes in the HDL composition and presence of proatherogenic lipidemia could, at least partly, be associated with a compensatory stimulation of PON1 lactonase activity.…”
Section: Discussionsupporting
confidence: 78%
“…Consistent with our findings, NLA was also increased in patients with coronary artery disease (CAD) (24). Recent studies have shown that HDLs from CAD patients enriched in PON1 (53) and proatherogenic small and density LDLs tend to be associated with increased PON1 activity (54). Based on these findings, we speculate that PCOS-related changes in the HDL composition and presence of proatherogenic lipidemia could, at least partly, be associated with a compensatory stimulation of PON1 lactonase activity.…”
Section: Discussionsupporting
confidence: 78%
“…As one of the components of metabolic syndrome, dyslipidemia is linked to chronic low-grade inflammation [5], oxidative stress [6,7], and insulin resistance [8], all of which may enhance CRC carcinogenesis. Ghandehari et al [9] using the National Health and Nutrition Examination Survey (NHANES) 2003-2004 data among US adults aged 20 and older found that nearly 51.4 million US adults demonstrated undesirable levels of high-density lipoprotein cholesterol (HDL cholesterol) and triglyceride and 36.1 million elevated low-density lipoprotein cholesterol (LDL cholesterol).…”
Section: Introductionmentioning
confidence: 99%
“…Fernandez et al [54] showed that HDL-C concentration was directly correlated to HDL diameter increase. According to Vekic et al [55] larger lipoprotein diameter subclasses (HDL2a and HDL2b) are negatively correlated with CVD. By contrast, smaller ones (HDL3a, HDL3b and HDL3c) are positively correlated.…”
Section: F S Marques Et Al Journal Of Biophysical Chemistrymentioning
confidence: 98%